El Homo faber de Max Frisch como punto de partida para el desarrollo de nuevos modelos en la literatura suiza - Hernández, Isabel (Revista de Filología Alemana, 2002)
Max Frisch’s prose trilogy, formed by the novels Stiller, Homo faber and Mein Name sei Gantenbein, brought about the thematic formal renovation of the German prose throughout the second half of the twentieth century. This fact can be appreciated in many of the novels written in the German part of Switzerland during the 1970s and the 1980s since they refer, thematically or structurally, to the most significant of the three, Homo faber. This article intends to offer a succint view of this reality and begins with an analysis of the internal and external structures of that novel.